Genetically Modified Rice Adoption: Implications for Welfare and Poverty Alleviation - Anderson, Kym (World Bank, Washington, D.C., 2013)
The first generation of genetically modified (GM) crop varieties sought to increase producer profitability through cost reductions or higher yields, while the next generation of GM food research is focusing on breeding for attributes of interest to consumers. Golden Rice, for example, has been genetically engineered to contain a higher level of vitamin A and thereby boost the health of poor people in developing countries. This paper analyzes the potential economic effects of adopting both types of innovation in Asia, including its impact on rice producers and consumers. It does so using the global economy-wide computable general equilibrium model known as GTAP. The results suggest the farm productivity gains could be dwarfed by the welfare gains resulting from the potential health-enhancing attributes of golden rice, which would boost the productivity of unskilled workers among Asia's poor.